Java for parallel discrete event simulation: a survey. (18th July 2012) - Castilla, I.; Aguilar, R.M.; Callero, Y.
Since the early 1990s, when it was first released, Java has become one of the most widespread programming languages. Discrete Event Simulation (DES) and also Parallel Discrete Event Simulation (PDES) have attracted more and more projects which are Java–based. This paper presents a brief survey on the tools and facilities that make Java such an attractive option for parallel simulation developers. Nevertheless, several drawbacks and lacks of the language are also exposed.